Discursive Practices of Doctor-Patient Online-Communication (the Case of “Health.mail.ru”) - L. V. Iskanderova (Дискурс, 2020)
Introduction. Nowadays medical online services are evolving rapidly and become more and more popular. Telemedicine is developed as a part of the Russian government program “The medical system 4P”. However, doctor-patient online communication has rarely been the subject of research in modern sociology. Nevertheless, online-services are valuable resource for researchers to study and analyze information that is difficult to obtain in other ways.Methodology and sources. The paper is devoted to the research of doctor-patient discursive practices on the internet medical advice forums by the example of “Health.mail.ru”. The general method  of  research  is  critical  discourse  analysis,  based  on the theory and methodology of N. Fairclough, which gives an opportunity to make suggestions about  social practices using text analysis  and  discursive practices analysis. A non-reactive strategy was used in the empirical research. During the research 28 800 messages, which include 14 400 messages from patients and 14 400 messages from doctors, were analyzed. Data analysis was performed in the “R” program.Results and discussion. As a result, some assumptions about social practices and discursive practices on the online forum were formulated. The main patient’s goal on online forums is avoiding face-to-face interaction with doctors in a hospital. One of doctor’s goals is promoting their services. Interaction is carried out in a form of request from the patient and expert assessment from the doctor in response. Usually, patients send their messages anonymously. Doctors, by contrast, emphasize their identity. It helps them to maintain their image and to legitimate their expertise. Doctor’s and patient’s discourses are using special medical terminology, and they are not interpreting it. It demands from the patients being experts.Conclusion. Online communication is a new type of doctor-patient communication, which is more democratic, more complementary and more impersonal than face-to-face communication. Usually doctor-patient online communication on the internet medical advice forums does not involve thorough analysis of individual patient’s situation and maintaining sustainable interpersonal relationships.